2010
DOI: 10.1253/circj.cj-09-0692
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Catechins Improve Human Forearm Endothelial Dysfunction and Have Antiatherosclerotic Effects in Smokers

Abstract: Background: Because green tea reduces cardiovascular and cerebrovascular risk, the purpose of this study aimed to elucidate the effect of green tea catechins (GTC) on endothelial dysfunction in smokers. Methods and Results:The 30 healthy male smokers were divided into 3 groups and given green tea beverages containing 0 mg (control group), 80 mg (medium-dose group) or 580 mg (high-dose group) of GTC daily for 2 weeks. Endothelial-dependent and-independent vasodilatation was investigated by measuring the forearm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…27 In contrast, it is widely accepted that the impairment of MetS status substantially promotes the progression of atherosclerosis 28 and increases the risk of CVD. 1 Also, another study on a cohort of 5,033 individuals with the same characteristics as the present subjects suggested that the exposure to MetS would explain at least in part the increasing risk of excessive carotid plaque in past smokers.…”
Section: Discussionmentioning
confidence: 99%
“…27 In contrast, it is widely accepted that the impairment of MetS status substantially promotes the progression of atherosclerosis 28 and increases the risk of CVD. 1 Also, another study on a cohort of 5,033 individuals with the same characteristics as the present subjects suggested that the exposure to MetS would explain at least in part the increasing risk of excessive carotid plaque in past smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Catechin is, however, a non-specific antioxidant that displays large cardio-protective properties [45], including anti-inflammatory properties [35,52]. To achieve significant beneficial effects against cardiovascular diseases, frequent and habitual consumption of catechins present in green tea is required [35,38,54]. In the present study, beneficial functional effects of long-term chronic catechin treatment were associated with reduced aortic plaque formation and aortic oxidative stress (but not cerebral oxidative stress), as we previously reported [12], and normalization of blood pressure in ATX mice.…”
Section: Discussionmentioning
confidence: 99%
“…Catechins are important components of green tea polyphenols with numerous favorable biological functions, including anti-inflammatory, anti-oxidative, anti-atherosclerotic, anticarcinogenic and anti-arthritic effects in humans (1)(2)(3). Green tea mainly contains four catechins, epicatechin, epigallocatechin, epicatechin gallate and (-)-epigallocatechin gallate (EGCG), and among them EGCG is the most abundant (4).…”
Section: Introductionmentioning
confidence: 99%